Development of landslide early wa rning system by online GPS in Central Java, Indonesia - Aditya, Trias (2010)
Lack of landslide early warning in a vulnerable area has seriously resulted in poor awareness and preparedness for landslide disasters, and accordingly brings to the increasing numbers of casualties. Therefore this research was conducted with the main purpose to develop landslide monitoring and early warning system which is supported by online GPS (Global Positioning System) and community empowerment in Tengklik Village, Tawangmangu District, Karanganyar Region, Central Java Province. Indeed, this study is very important to support policy decisions related to the early warning to landslide hazards in the community of the village. Integrated discipline of study is the approach of this research, which includes the study on engineering geology and geotechnics (civil engineering) to conduct landslide hazard mapping for site selection of early warning installment and understanding the mechanism of landslide that should be monitored. This understanding is important for further development of the design of the appropriate early warning system. Accordingly, the integrated study of geodetic engineering and electrical engineering are responsible for developing the online GPS system which is connected to a website. In line with this integrated study, social mapping for identifying community perception and aspiration were conducted in order to develop an appropriate approach and method to motivate and empower the community living in the installed early warning site, and thus the effectiveness of the operation and maintenance of such system. Finally, this study has been succeeded-to produce a monitoring system to detect ground movement landslides using internet-based GPS (Online GPS) with a relatively low cost by using the OEM GPS L1. The developed system was built using Matlab Web Server for processing GPS data which was supported by some web programming language. Indeed, the system has been able to indicate the movement of the GPS position on the field and showing landslide risk indicators (green, yellow, red level of warning) graphically for use in a landslide early warning. Obviously, this online GPS system offers such an easy monitoring system in disaster prone areas. The system is equipped with automation facilities of disaster notification and is expected to assist the decision making process for early warning with respect to the landslide disaster risk reduction efforts.